PENDAMPINGAN PEMBELAJARAN ILMU TAJWID DI TAMAN PENDIDIKAN AL QUR’AN RIYADHUL TAQWA - Shiva Sholiyana; Elva Riski Umami (khidmatan, 2024)
TPQ Riyadhul Taqwa faces significant constraints in its Read and Write Al-Qur'an (BTA) teaching and learning activities, particularly concerning the mastery and application of Ilmu Tajwid (the science of correct Qur'anic recitation). This condition hinders the achievement of optimal educational goals, considering that Ilmu Tajwid—the knowledge branch dictating the proper way to recite the Qur'an—is considered fardhu 'ain (an individual obligation). Therefore, this Community Service (PkM) activity aims to: 1) Enhance the capacity and understanding of TPQ Riyadhul Taqwa teachers in implementing Tajwid instruction; 2) Improve the students' understanding and practical application of Tajwid; and 3) Develop the teachers' skills in delivering Tajwid material creatively, engagingly, and comprehensibly. The mentoring method employed interactive and fun learning approaches, coupled with direct practice (talaqqi). The outcome of this PkM activity includes additional insight and skills for the educators, as well as increased enthusiasm and motivation among the students. The students are now better equipped to practice various Tajwid rules in Al-Qur'an verses accurately through enjoyable and easily understandable methods.